1990
DOI: 10.3168/jds.s0022-0302(90)78756-5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between the Respiratory Burst Activity of Neutrophil Leukocytes and Experimentally Induced Escherichia coli Mastitis in Cows

Abstract: The respiratory burst activity of neutrophil leukocytes from bovine peripheral blood was studied before and during an experimentally induced Escherichia coli mastitis. The competence of neutrophils to generate reactive oxygen species following stimulation with opsonized particles prior to infection was negatively correlated with severity of subsequently induced E. coli mastitis. In the presence of the soluble activator, phorbol myristate acetate, no such correlation was obtained. However, combination of blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
113
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 12 publications
9
113
2
Order By: Relevance
“…The CL of blood PMN was calculated with the same formula as for milk PMN, applying the corrections described by Heyneman et al [15] for eosinophils contributing to the ROI production in the samples, considering that the CL response of eosinophils is five times higher than that of PMN.…”
Section: Chemiluminescence Assaymentioning
confidence: 99%
See 3 more Smart Citations
“…The CL of blood PMN was calculated with the same formula as for milk PMN, applying the corrections described by Heyneman et al [15] for eosinophils contributing to the ROI production in the samples, considering that the CL response of eosinophils is five times higher than that of PMN.…”
Section: Chemiluminescence Assaymentioning
confidence: 99%
“…Polymorphonuclear leukocytes (PMN) are important components of the cellular host defense in protecting cows against Escherichia coli infection within the mammary gland [5,15,19,21,39]. Acute E. coli mastitis in early lactating cows is sometimes accompanied by severe general clinical symptoms such as fever and a sudden decrease of milk production in non-injected (non-inflamed) quarters [16,24,37].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In infected mammary glands PMN are the predominant cell type. Earlier studies have shown that SCC prior to infection determines the sensitivity and severity of mastitis in lactating cows [4,21]. The protective effect of a high SCC against mastitis pathogens is well known [15].…”
Section: Introductionmentioning
confidence: 99%